2022
DOI: 10.1111/pce.14376
|View full text |Cite
|
Sign up to set email alerts
|

Predicting resilience through the lens of competing adjustments to vegetation function

Abstract: There is a pressing need to better understand ecosystem resilience to droughts and heatwaves. Eco‐evolutionary optimization approaches have been proposed as means to build this understanding in land surface models and improve their predictive capability, but competing approaches are yet to be tested together. Here, we coupled approaches that optimize canopy gas exchange and leaf nitrogen investment, respectively, extending both approaches to account for hydraulic impairment. We assessed model predictions using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 108 publications
0
17
0
Order By: Relevance
“…Second, there was observed damage to the canopy, whereby much of the upper sunlit layer was scorched during the drought. In addition to drought‐induced leaf abscission (Figure S3f), which can protect the xylem of more costly woody tissues (Nadal‐Sala et al, 2021; Sabot et al, 2022), a considerable amount of necrotic leaf tissue remained intact in the upper sunlit canopy (Kravitz et al, 2016). Thus, large quantities of light would have been absorbed by physiologically inactive leaves, thereby limiting LUE recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there was observed damage to the canopy, whereby much of the upper sunlit layer was scorched during the drought. In addition to drought‐induced leaf abscission (Figure S3f), which can protect the xylem of more costly woody tissues (Nadal‐Sala et al, 2021; Sabot et al, 2022), a considerable amount of necrotic leaf tissue remained intact in the upper sunlit canopy (Kravitz et al, 2016). Thus, large quantities of light would have been absorbed by physiologically inactive leaves, thereby limiting LUE recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, changes in LMA are directly tied to changes in whole‐plant leaf area and HV, making it potentially difficult to isolate leaf‐level plasticity from whole‐plant structural changes. Joint experimental and modelling studies have suggested that leaf shedding or reduced leaf growth is the most effective strategy to protect trees from subsequent drought events (Nadal‐Sala et al ., 2021; Sabot et al ., 2022). This is supported by evidence from local and global environmental gradients, where plants in drier environments tend to have greater HV to minimise water losses (Mencuccini et al ., 2019; Anderegg et al ., 2021).…”
Section: Summarising Plasticity In Key Traits In Response To Droughtmentioning
confidence: 99%
“…2 and needs to be accounted for when predicting range dynamics (Chuine, 2010). Because transpiration and water demand from the canopy are largely determined by the amount of evaporating surface, tissuelevel exposure to drought is controlled, to an important extent, by the dynamics of leaf area (Wolfe et al, 2016;Sabot et al, 2022).…”
Section: Accounting For Environmental Variability and Local Exposurementioning
confidence: 99%